Zipf zipped - Volker Nitsch (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2004)
In this paper, I provide a quantitative review of the empirical literature on Zipf's law for cities; the meta-analysis combines 515 estimates from 29 studies. I find that the combined estimate of the Zipf coefficient is significantly larger than 1.0. This finding implies that cities are on average more evenly distributed than suggested by (a strict interpretation of) Zipf's law. I also identify several features that account for differences across the individual point estimates.
Keywords: R12; R15; 330; Zipf's law; size distribution of cities; rank size rule; meta-analysis